From Severe Aortic Stenosis to Mitral TEER - Tasha M. Heller, MD; Sara Lezcano, DO; Ram Hirpara, DO; Alexander K. Patel, DO; Yordanka Reyna, MD; Faraaz Mushtaq, DO; Mohamed Osman, MD; Arnoux Blanchard, MD (JACC: Case Reports)
Background: Systolic anterior motion (SAM) and dynamic left ventricular outflow tract obstruction (LVOTO) is a well-described phenomenon in hypertrophic obstructive cardiomyopathy and rarely reported after surgical aortic valve replacement (AVR). Case Summary: We present the first reported case of SAM and LVOTO developing intraoperatively after surgical AVR for severe bicuspid aortic valve stenosis necessitating mitral transcatheter edge-to-edge repair (TEER) with the MitraClip. Optimal titration of pharmacologic management was not sufficient to relieve LVOTO in our patient. Why Beyond the Guidelines: Despite management following conventional guidelines, the patient remained in critical condition. TEER with the MitraClip led to a reduction in SAM and optimization of his cardiovascular profile. Discussion: There is limited literature regarding intervention with TEER on post-AVR patients. Take-Home Message: LVOTO can present suddenly, as in our case, necessitating a multispecialty approach to unconventional interventions to stabilize a critically ill patient.